Pengaruh Ketebalan Mulsa Serbuk Gergaji Kayu Jati dan Konsentrasi Teh Kompos terhadap Pertumbuhan dan Hasil Jagung Berondong Lokal (Zea mays Everta) - Cornelio Clara Lede (Savana Cendana, 2019)
This study aims to determine the effect of teak sawdust mulch thickness and compost tea concentration on teh growth and yield of local popcorn (Zea mays Everta). The study was conducted at teh Faperta experimental garden at teh University of Timor in December 2016-April 2017 using a 3x3 factorial randomized block design repeated 3 times tehn furtehr tested with the DMRT test at teh 5% level. The first factor is the thickness of the sawdust mulch (M) which consists of 3 levels, namely no mulch (M0), 1 cm (M1) and 3 cm (M2) thickness of mulch, and teh second factor is the concentration ratio of compost tea to water (K) which consists of 3 levels, namely without compost tea (K0), compost tea 1 L: 5 L water (K1) and compost tea 1 L: 10 L water (K2). The results showed that tehre was no interaction between the thickness of the mulch and teh concentration of compost tea. the 3 cm thickness of mulch treatment produced the highest corn shelled (0.60 t / ha) with the percentage of finished popcorn (64.22%) while the compost tea concentration treatment was significantly at a concentration of 1:10 to produce teh highest shelled corn that was equal to 0.53 t / ha with teh percentage of finished popcorn (61.11%).